Formulation of compact powder from rice fermentation using Response Surface Methodology (RSM) - Nurfarisha Ahmad Fironus Firdaus; Mohd Hafizuddin Muhamad; Hassimi Abu Hasan; Noorhisham Tan Kofli (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cooling powder is a traditional local cosmetic product produced from natural fermentation of rice. This product has been passed down until today due to its beneficial properties and is believed to have a cooling effect on the user. In current market, this product is still being sell in its traditional form which is in the form of powder and beads which are difficult to use. At the same time, there are concerns regarding safety talc-based cosmetics due to its potential contamination with asbestos, a toxic mineral. Therefore, this study is conducted to modernize this increasingly forgotten traditional product into a compact powder and replace the talc composition with cooling powder. Binding agents and oil absorbing agents are added to produce better quality of compact powder. The objective of this study is to determine the best composition of powder, binding agent and oil absorbing agent for compact powder formulations by using Response Surface Methodology (RSM), where Central Composite Design (CCD) is utilized. The cooling powder composition studied for the compact powder formulation are 50%, 55% and 60%. Meanwhile, kaolin is added as oil absorbing agent with compositions of 20%, 25% and 30%. Virgin coconut oil is added as binding agent at varied composition of 5%, 7.5% and 10%. Two types of drop tests are carried out to investigate the durability of the compact powder formulation, which are weight and height drop tests. Oil absorption capacity test is performed to evaluate the effectiveness of the compact powder formulations in absorbing oil.